Caracterizando Estratégias de Domínio Espacial para Gerenciamento de Regras em Redes Definidas por Software - Araújo, Gustavo de; Marotta, Marcelo; Wickboldt, Juliano; Both, Cristiano; Gaspary, Luciano; Rochol, Juergen; Granville, Lisandro (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
Software-Defined Networks (SDN) based on Openflow protocol perform data forwarding through flow tables using match/action mechanisms. These tables have limited rules storage capacity, restricting network scalability and performance. Considering these restrictions, the main strategies for managing spatial domain rules, i.e., flow agregation and multiple flow tables, are promising to use the available storage space of the tables. These strategies impact packet processing in different ways, influencing the performance of the forwarding devices and the network. In spite of the impact, the comparison between flow aggregation and multiple flow tables is poorly exploited, leaving open the definition of which strategy is more appropriate for a network considering its topology and workload. In this article a quantitative characterization is proposed, defining the gains brought by these spatial domain strategies for forwarding devices and in different topologies.